DIFFERENTIAL HISTOPATHOLOGICAL DIAGNOSIS BETWEEN MASTITIS AND INFILTRATIVE DUCTAL CARCINOMA OF THE BREAST: A RETROSPECTIVE ANALYSIS - Ruziyev Sh.I.,; Ravshanova N.B., (Central Asian Journal of Medicine, 2025)
Background: Breast lesions presenting as infiltrative processes pose a significant diagnostic challenge, especially in differentiating benign inflammatory conditions such as mastitis from malignant tumors like infiltrative ductal carcinoma (IDC). Misdiagnosis may lead to unnecessary surgery or delayed cancer treatment. Objective: To evaluate the diagnostic value of histopathological criteria in distinguishing mastitis from infiltrative ductal carcinoma in breast tissue specimens. Methods: A retrospective analysis of 60 female patients was conducted: 45 diagnosed with mastitis and 15 with IDC. H&E-stained sections were examined for cellular atypia, mitotic activity, stromal changes, necrosis, lymphocytic infiltrate, and ductal architecture. Comparative statistical analysis was performed to identify key differentiating features. Results: Cytological atypia, frequent mitoses, necrosis, desmoplastic stromal reaction, and loss of ductal architecture were significantly associated with IDC (p < 0.001). Mastitis cases exhibited preserved ductal structures, dense lymphocytic infiltrates, and absence of malignant features. The most reliable distinguishing criteria were cytological atypia and desmoplasia. Conclusion: Histopathological evaluation remains the gold standard for differentiating mastitis from IDC. A structured assessment of key features allows for accurate diagnosis, prevents overtreatment of benign conditions, and ensures timely cancer management.